THE EFFECT OF PHYSICAL ACTIVITY ON HYPERTENSION- LITERATURE REVIEW - Adam Solarz; Szymon Szabelski; Katarzyna Skibicka; Joanna Kryślak; Maciej Sokołowski; Karolina Oskroba (International Journal of Innovative Technologies in Social Science, 2025)
Hypertension remains one of the leading preventable causes of cardiovascular morbidity and mortality worldwide. Although pharmacological interventions are effective, they often fail to address the underlying behavioural and physiological determinants of high blood pressure. Physical activity is a cornerstone of non-pharmacological management strategies, exerting broad and sustained benefits on vascular function, autonomic regulation, and overall cardiovascular health. This literature review synthesises evidence from thirty peer-reviewed studies and meta-analyses published between 2010 and 2025, evaluating the effects of various exercise modalities including aerobic, resistance, isometric, and combined training on blood pressure reduction and cardiovascular outcomes in hypertensive populations [1-30]. Findings indicate that regular participation in structured physical activity produces clinically significant reductions in both systolic and diastolic blood pressure, with average decreases of 5-10 mmHg observed across modalities. Aerobic exercise demonstrates the most consistent antihypertensive effect, whereas resistance and isometric training appear beneficial as complementary interventions that enhance muscular strength, vascular elasticity, and endothelial function. The review also highlights dose-response relationships between exercise intensity, frequency, and blood pressure control, along with evidence that physical activity mitigates inflammation, oxidative stress, and arterial stiffness. These findings underscore the role of physical exercise as an evidence-based, first-line intervention for both the prevention and management of hypertension. Objective: This review aims to synthesize current evidence on the effects of different forms of physical activity on hypertension, examining how aerobic, resistance, isometric, and combined exercise influence blood pressure regulation and cardiovascular health. Material and Methods: A literature review from PubMed and Google Scholar.